(untitled) (Texas Journal of Philology, Culture and History, 2023)
This article interprets the trends that took place in the cultural life of Uzbekistan in the 30s of the XX century, explains the requirements of that period and its influence on subsequent levels of cultural development. It was analyzed that the culture of the period of Soviet colonialism differs from the cultural progress of other periods by its contradictory aspects and positive and negative characteristics. The main feature of this period is based on the subordination of all spheres of life, including the sphere of spiritual culture, to communist ideology